Al-Muqawwimāt al Fikriyyah li al-ilmanīyah - Muslim Nasution (Al-Jami'ah: Journal of Islamic Studies, 2002)
Nowadays, secular life has greatly influenced modern society. It is ordinary if secular life has swept out of Western society because, indeed, secularism was born there with the background of Christianity. However, it is different if secular life also influences Muslim societies, because it contradictory to Islamic teachings. The widespread of secularism in Muslim societies is the result of the propaganda of secularists. Even, they made a kind of academic fraud by using the Arabic word 'ilmaniyyah to legalize their thought. This article is trying to reveal the term of secularism especially in Arabic by tracing its original meaning in Greek. The writer believes that the translation of the word secularism as 'ilmaniyyah is misleading. This article is also trying to explore the early history of secularism, and various backgrounds of thoughts of that time.[Kehidupan sekuler sudah sedemikian rupa mewarnai masyarakat modern dewasa ini. Kalau kondisi seperti ini melanda masyarakat Barat adalah suatu hal yang wajar karena pemikiran sekularisme memang muncul dari sana dengan Kristen sebagai agama yang berperan melatarbelakangi munculnya pemikiran tersebut. Persoalannya menjadi lain ketika kehidupan sekuler juga melanda masyarakat muslim yang jelas-jelas bertentangan dengan ajaran Islam itu sendiri. Hal ini tidak terlepas dari propaganda yang begitu gencar yang dilakukan oleh kaum sekuler, bahkan ke tingkat pembohongan akademik seperti pemakaian istilah sekuler dalam bahasa Arab dengan 'ilmaniyah dimana diambil dari kata 'ilm. Makalah ini berusaha mengungkap istilah sekularisme khususnya dalam bahasa arab, sejarah kemunculannya dan berbagai landasan pemikiran sekularisme itu sendiri.]